The Role of The Supervision of The Principal In Improving The Quality of Education in The State Ibtidaiyah Madrasah, Langkat Regency - Amiruddin Siahaan; Mansyur Hidayat Pasaribu; Suparliadi Suparliadi; Muhammad Rizki Syahputra; Ahmad Mukhlasin (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The purpose of this paper is to discuss the role of the academic supervision of the madrasa principal in improving the quality of education in the State Madrasah Ibtidaiyah Langkat Regency, this study uses a descriptive qualitative method. The findings of this study are (1) the activities of the principal as a supervisor in coordinating activities, including coordination of guiding activities via microphone, coordination between teachers in the field of study, making roster and positioning teachers according to their field of expertise; (2) The activities of the principal as a supervisor in providing consultants, include (a) individual techniques (class visits, personal observation and guidance in the office) and (b) group techniques (meetings or regular meetings every month); (3) The activities of the principal as a supervisor in the group leader, in the form of leading firmly, helping or facilitating teachers to develop their potential, providing direction and guidance related to general teaching guidelines, as well as meeting the needs of teachers in teaching; (4) The activities of the principal as a supervisor in the evaluator, include providing assistance in assessing learning processes and outcomes, helping teachers choose the right method according to the curriculum; (5) Factors that affect education supervision in MIN Langkat Regency a) inhibiting factors include: teacher hours are too tight so it is difficult to hold meetings, the head of the foundation that limits all activities, the skills and expertise of the principal who are lacking in carrying out their roles, the principal's time is limited.